Impaired efficacy of spinal presynaptic mechanisms in spastic stroke patients - Lamy, Jean-Charles; Wargon, Isabelle; Mazevet, Dominique; Ghanim, Zaïd; Pradat-Diehl, Pascale; Katz, Rose (Brain (London, England : 1878), 2009)
Pathophysiological mechanisms underlying spasticity have been the subject of many studies. These studies performed in various kinds of spastic patients have revealed abnormalities in many spinal pathways controlling motoneurone discharge. Unfortunately, the pathophysiological mechanisms responsible for the development of spasticity remains nevertheless largely unknown since most of the previous studies failed to reveal a link between the characteristics of spasticity (severity, time course) and that of the dysfunction of a given perturbed spinal pathway. In the present series of experiments, we focused on the study of presynaptic mechanisms acting at the synapse fibre Ia—motoneurone since monosynaptic reflexes are enhanced in spasticity. Two presynaptic mechanisms have been described in both animals and humans: presynaptic Ia inhibition and post-activation depression. By increasing the number of subjects in comparison with previous studies (87 patients and 42 healthy controls) we have been able to show that these two mechanisms are unequally impaired in stroke patients depending on (i) the duration of the disease (acute, defined as less than 3 months after the causal lesion, or chronic, defined as more than 9 months after the causal lesion), (ii) the side considered (affected or unaffected) and (iii) the severity of spasticity. In this respect, only post-activation depression amount was found to be highly correlated with the severity of spasticity. Although not a definitive proof, this correlation between severity of spasticity and changes in a given spinal pathway lead us to conclude that the impairment of post-activation depression is likely one of the mechanisms underlying spasticity. On the contrary, changes in presynaptic Ia inhibition appear to be a simple epiphenomenon, i.e. a basic correlate of the brain lesions. It is argued that plastic changes develop from the disuse due to motor command impairment in both pathways.